Criptococcus Meningitis and Acquired Immunedeficiency, Experience at The Hospital Nacional Dos De Mayo in Lima, Perú - Fernández, Alejandro (1996)
Objectives: To determine the incidence of criptococcus meningitis (CM) in patients who died with HIV infection stage AIDS at the Hospital National Dos de Mayo (HNDM).Methods: A retrospective study of 21 patients who died with CM and AIDS since January 1991 until December 1994 at the HNDM.Results: The incidence of CM in patients with AIDS was 10,2%. All were males. The highest incidence was between 26 and 30 years. Risk factors found were: homosexuality in 38%, bisexuality in 33,1%, and heterosexuality promiscuous in 26,6%. In addition, 38% of the patients showed alcohol, cocaine and marihuana abuse. ELISA and Western Blot tests for HIV were used. The diagnosis of CM was made by finding criptococcus neoformans in CSF, by direct exam, 76,2%; by culture,14,2% and by both methods 8,5%. We found lymphocytopenia in 61,9% of patients and hypoalbuminemia in 62,0%.Conclusions: CM is a frequent complication of HIV stage AIDS, with high mortality rates. Males are more affected, with highest predominance between 26 and 30 years. The heterosexual promiscuous population is importantly affected. Most frequent symptoms were headache, nausea, vomiting and general malaise. Serum lymphocytopenia and hypoalbuminemia are bad prognosis predictors. Survivorship was less than a year in 90,5%.